التعليم الإلكتروني كمدخل لإصلاح قطاع التعليم العالي والبحث العلمي بالجزائر - سايح جبور, علي (roa, 2020)
ﻧﺴﻌﻰ ﻣﻦ ﺧﻼﻝ ﻫﺬﻩ ﺍﻟﺪﺭﺍﺳﺔ ﺍﻟﻰ ﺗﺴﻠﻴﻂ ﺍﻟﻀﻮﺀ ﻋﻠﻰ ﻛﻴﻔﻴﺔ ﺍﻻﻋﺘﻤﺎﺩ ﻋﻠﻰ ﺗﻘﻨﻴﺎﺕ ﺍﻻﻧﺘﺮﻧﺖ ﻓﻲ ﺗﻄﻮﻳﺮ ﺍﻟﺘﻌﻠﻴﻢ ﺍﻻﻟﻜﺘﺮﻭﻧﻲ ﻭﺗﺜﺒﻴﺘﻪ ﻭﺍﻻﺳﺘﻔﺎﺩﺓ ﻣﻨﻪ ﺑﻘﻄﺎﻉ ﺍﻟﺘﻌﻠﻴﻢ ﺍﻟﻌﺎﻟﻲ ﻭﺍﻟﺒﺤﺚ ﺍﻟﻌﻠﻤﻲ. ﻣﻦ ﻫﻨﺎ ﺟﺎﺀ ﺳﺆﺍﻝ ﺍﻹﺷﻜﺎﻟﻴﺔ ﻭﻓﻖ ﺍﻟﺼﻴﺎﻏﺔ ﺍﻟﺘﺎﻟﻴﺔ: ﺇﻟﻲ ﺃﻱ ﻣﺪﻯ ﻳﻤﻜﻦ ﻟﻠﺠﺎﻣﻌﺔ ﺍﻟﺠﺰﺍﺋﺮﻳﺔ ﺗﺒﻨﻲ ﻫﺬﺍ ﺍﻟﻨﻤﻂ ﻣﻦ ﺍﻟﺘﻌﻠﻴﻢ؟ ﻭﻫﻞ ﺍﻻﻋﺘﻤﺎﺩ ﻋﻠﻰ ﻫﺬﺍ ﺍﻟﻨﻤﻂ ﺑﺎﻟﺘﻮﺍﺯﻱ ﻣﻊ ﺇﺑﻘﺎﺀ ﺍﻟﺘﻌﻠﻴﻢ ﺍﻟﺘﻘﻠﻴﺪﻱ ﻗﺎﺩﺭ ﻋﻠﻰ ﺣﻞ ﻣﺸﺎﻛﻞ ﺍﻟﻘﻄﺎﻉ؟ ﻫﻞ ﺍﻟﺠﺎﻣﻌﺔ ﺍﻟﺠﺰﺍﺋﺮﻳﺔ ﻗﺎﺩﺭﺓ ﻋﻠﻰ ﺍﺳﺘﻴﻌﺎﺏ ﺍﻟﺘﺰﺍﻳﺪ ﺍﻟﻤﺴﺘﻤﺮ ﻓﻲ ﺃﻋﺪﺍﺩ ﺍﻟﻄﻠﺒﺔ ﺍﻟﻮﺍﻓﺪﻳﻦ ﺇﻟﻴﻬﺎ ﻛﻞ ﺳﻨﺔ ﻣﻊ ﻣﺎ ﺗﺘﻮﻓﺮ ﻋﻠﻴﻪ ﻣﻦ ﻗﺪﺭﺍﺕ ﻣﺎﻟﻴﺔ ﻟﺘﻠﺒﻴﺔ ﺣﺎﺟﻴﺎﺕ ﺍﻟﻄﻠﺒﺔ ﺍﻟﺒﻴﺪﺍﻏﻮﺟﻴﺔ ﻭﺍﻻﺟﺘﻤﺎﻋﻴﺔ؟ الكلماتالمفتاحية : اﻟﺘﻌﻠﻴﻢ ﺍﻻﻟﻜﺘﺮﻭﻧﻲ، ﺍﻟﺠﺎﻣﻌﺔ ﺍﻟﺠﺰﺍﺋﺮﻳﺔ، ﺍﻟﻄﺮﻕ ﺍﻟﺤﺪﻳﺜﺔ ﻓﻲ ﺍﻟﺘﻌﻠﻴﻢ، ﺗﻘﻨﻴﺎﺕ ﺍﻹﻋﻼﻡ ﻭﺍﻻﺗﺼﺎﻻﺕ ﺍﻟﺤﺪﻳﺜﺔ، ﺍﻟﺘﻌﻠﻴﻢ ﺍﻻﻓﺘﺮﺍﺿﻲ، ﺍﻻﻧﺘﺮﻧﺖ.   Abstract: This study attempts to shed light on the applications of Internet in the development of E-learning and its integration in the sector of higher education and scientific research. It is in this light that comes the statement of the problem : To what extent can the Algerian university adopt the E-learning ? And with its adoption in parallel with the traditional model, will it be possible to solve problems ? Therefore, some sub-questions may be asked : ־Is the Algerian University in a good position to respond to the increase of the students number and has it enough financial and educational resources that meet the student’s expectations, and social development ? Key words : Algerian university, E-learning, distance learning, new teaching methods, Internet, information technology and communication, TIC applications